Impact of Piriformospora indica on various characteristics of tomatoes during nickel nitrate stress under aeroponic and greenhouse conditions - Mahmoodi, Nazanin; Movahedi, Zahra; Ghabooli, Mehdi (Frontiers in Microbiology, 2023)
As an essential nutrient for plant growth, nickel's (Ni) requirement is very low, and its augmented level causes environmental pollution and toxicity. Being a root endophytic fungus, Piriformospora indica (P. indica) can be beneficial to many plants under stress and non-stress conditions, particularly in terms of their improved growth performance. P. indica, as evidenced, enhances tolerance and resistance in most plants once they experience a range of stresses caused by biotic and abiotic factors, e.g., diseases and heavy metals. Against this background, the positive effects of P. indica on the tomato plants under Ni-induced stress (300, 600, and 900 mg L−1) were analyzed in three experiments at labs, at greenhouses, and via aeroponics in this study. The growth traits of the tomato plants, such as root length (RL) and root dry weight (RDW), were accordingly found to be positively boosted in the cases treated with P. indica compared to the non-treated ones. Treating with P. indica also thwarted the negative effects of Ni on some biochemical traits, including anthocyanin (Anth), proline (Pro), catalase (CAT), and glutathione peroxidase (GPx), while significantly minimizing the adverse impacts of this heavy metal at different levels on hydrogen peroxide (H2O2). Despite this, the Ni-stressed plants indicated much better traits in the presence of this fungus, compared with the non-treated ones, in most of the cases measured. Moreover, the photosynthetic pigments, i.e., chlorophyll a and b (Chl a & b) and carotenoid content (Carrot), were significantly higher in the tomato plants treated with P. indica under high Ni-induced stress as compared with the non-treated ones under non-Ni conditions, in which these pigments were low. The pro-production was further observed all through the P. indica inoculation, which could aid the treated plants in becoming Ni-stress-tolerant. Finally, the current study contributed to a better understanding of how to use the P. indica symbiosis to induce heavy metal tolerance in tomato plants, such as Ni, to meet the goals of sustainable agriculture.